PathwayMatcher: proteoform-centric network construction enables fine-granularity multiomics pathway mapping. Issue 8 (30th July 2019) - Sánchez, Luis Francisco Hernández; Burger, Bram; Horro, Carlos; Fabregat, Antonio; Johansson, Stefan; Njølstad, Pål Rasmus; Barsnes, Harald; Hermjakob, Henning; Vaudel, Marc
Abstract: Background: Mapping biomedical data to functional knowledge is an essential task in bioinformatics and can be achieved by querying identifiers ( e.g ., gene sets) in pathway knowledge bases. However, the isoform and posttranslational modification states of proteins are lost when converting input and pathways into gene-centric lists. Findings: Based on the Reactome knowledge base, we built a network of protein-protein interactions accounting for the documented isoform and modification statuses of proteins. We then implemented a command line application called PathwayMatcher (github.com/PathwayAnalysisPlatform/PathwayMatcher) to query this network. PathwayMatcher supports multiple types of omics data as input and outputs the possibly affected biochemical reactions, subnetworks, and pathways. Conclusions: PathwayMatcher enables refining the network representation of pathways by including proteoforms defined as protein isoforms with posttranslational modifications. The specificity of pathway analyses is hence adapted to different levels of granularity, and it becomes possible to distinguish interactions between different forms of the same protein.